Fruits of learning : the transfer of encyclopaedic knowledge in the early Middle Ages - Bremmer, Rolf H.; Dekker, Cornelis; Storehouses of Wholesome Learning (Project) (Mediaevalia Groningana, 2016)
Encyclopaedic knowledge - factual knowledge of the divine and human worlds - had profound effects on intellectual activities in the early Middle Ages and its aftermath. Authors and scribes were raised in an intellectual and didactic tradition in which the acquisition and development of encyclopaedic knowledge was highly valued. Their concern with the elementary aspects of time, language, world history, God's creation and the Bible informed their activities as compilers of manuscripts or as producers of texts. They reaped the fruits of the learning that had grown over the centuries, digested them, or discarded them, or caused them to re-emerge after a long period of time and be used for purposes quite different from those for which they had originally been cultivated. The varieties of such fruit are as diverse as encyclopaedic learning itself, involving musicology, epistolography, liturgy, the study of grammar, codicology, the establishment of reading programmes, the writing of history and, perhaps most prominently, the compilation and promulgation of glosses and glossaries - one of the most essential disciplines in early medieval learning. The present volume casts light on the way in which encyclopaedic knowledge came to fruition in the ever expanding and diversifying world of medieval learning. Resulting from the fourth workshop in the 'Storehouses of Wholesome Learning' project, it builds on the foundations laid by its predecessors. The contributors discuss the influence of encyclopaedic knowledge in their respective fields of expertise. Their generous responses have provided a rich palette of new insights into medieval intellectual culture. Their articles deepen our understanding of medieval learning in its ability to instrumentalise the knowledge inherited from the classical world in the creation of new cultures of wisdom.
Keywords: To 1500; Language and languages : Glossaries, vocabularies, etc : Congresses; Learning and scholarship : History : Medieval, 500-1500 : Congresses; Manuscripts, English (Old) : Congresses; Manuscripts, Latin (Medieval and modern) : Europe : Congresses; Transmission of texts : Europe : History : To 1500 : Congresses; Language and languages; Learning and scholarship : Medieval; Manuscripts, English (Old); Manuscripts, Latin (Medieval and modern); Transmission of texts; Europe